Pelatihan Tata Kelola Manajemen dan Digital Marketing bagi Kelompok Pengrajin Budi Sangkar - Sarah Dien Hawa; Ririn Setyorini; Fuaida Nabyla (Jurnal Pemberdayaan Ekonomi, 2023)
Purpose: The purpose of this service aims to increase sales of bird cages to the Budi Sangka craftsman group. The Budi Sangkar craftsmen group is a group of bird cage craftsmen who are located in Banjarsari Village, Ajibarang, Banyumas. This service is carried out by accompanying and training the Budi Sangkar craftsman group in terms of management, digital marketing, and advertising/promotion style to increase the sales of the craftsmen group during the Covid-19 pandemic. Methodology: This service uses a methodology that is divided into 3 steps:1) team coordination with partners, 2) training and mentoring, and 3) monitoring and evaluation. Result: The result of the services show that partner’s sales and profit increased by doing: 1) counseling on management, 2) training on making marketing plans, 3) training on managing good human resources so that motivation and performance increase, 4) training and digital marketing assistance through social media and e-commerce, 5) training on promotional diction or language style in marketing/advertising/promotion that is appropriate and appropriate for HR to improve speaking and writing skills in promoting their craft, 6) training and assistance in managing social media, 7) training and assistance in making promotional flyers so that improve the company's brand image. Limitation: The limitation of this service has not been carried out continuously and requires continuity of mentoring activity. Contribution: The contribution is increasing the partner’s sales and profits.